Influence of alkyl chain length on the surface activity of antibacterial polymers derived from ROMP - Altay, Esra; Yapaoz, Melda Altikatoglu; Keskin, Bahadir; Yucesan, Gundog; Eren, Tarik (ELSEVIER SCIENCE BV, 2015)
The purpose of this study is to understand the antibacterial properties of cationic polymers on solid surfaces by investigating the structure-activity relationships. The polymer synthesis was carried via ring opening metathesis polymerization (ROMP) of oxanorbornene derivatives. Modulation of molecular weights and alkyl chain lengths of the polymers were studied to investigate the antibacterial properties on the glass surface. Fluorescein (Na salt) staining contact angle measurements were used to characterize the positive charge density and hydrophobicity on the polymer coated surfaces. Positive charge density for the surface coated polymers with molecular weights of 3000 and 10,000 g mol(-1) is observed to be in the range of 2.3-28.5 nmol cm(-2). The ROMP based cationic pyridinium polymer with hexyl unit exhibited the highest bactericidal efficiency against Escherichia coli on solid surface killing 99% of the bacteria in 5 min. However, phenyl and octyl functionalized quaternary pyridinium groups exhibited lower biocidal properties on the solid surfaces compared to their solution phase biocidal properties. Studying the effect of threshold polymer concentrations on the antibacterial properties indicated that changing the concentrations of polymer coatings on the solid surface dramatically influences antibacterial efficiency. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: ROMP; Biological applications of polymers; Antibacterial coatings; Selectivity; Structure-property relations; ANTIMICROBIAL POLYMERS; CHARGE-DENSITY; HEMOLYTIC ACTIVITIES; CATIONIC SURFACES; BLOCK-COPOLYMERS; SYNTHETIC MIMICS; METATHESIS; BACTERIA; PEPTIDES; CONTACT; Biophysics; Chemistry; Materials Science